Pakistan: Getting more from water - Young, William J.; Anwar, Arif; Bhatti, Tousif; Borgomeo, Edoardo; Davies, Stephen (World Bank, 2019)
This report builds on prior work to provide a new, comprehensive, and balanced view of water security in Pakistan, stressing the importance of the diverse social, environmental, and economic outcomes from water. The report highlights the complex water issues that Pakistan must tackle to improve water security and sheds new light on conventional assumptions around water. It seeks to elevate water security as an issue critical for national development. The report assesses current water security and identifies important water-related challenges that may hinder progress in economic and human development. It identifies unmitigated water-related risks, as well as opportunities where water can contribute to economic growth and poverty reduction. The report analyzes how the performance and architecture of the water sector are related to broader economic, social, and environmental outcomes. It models alternative economic trajectories to identify where intervention can lead to a more water-secure future. A consideration of water sector architecture and performance and how these determine outcome leads to recommendations for improving aspects of sector performance and adjusting sector architecture for better outcomes. The sector performance analysis considers (a) management of the water resource, (b) delivery of water services, and (c) mitigation of water-related risks. The description of sector architecture considers water governance, infrastructure, and financing.